Strategi Komunikasi Dakwah dalam Penguatan Literasi Ekonomi Syariah Masyarakat Muslim - Yeni Yasyah Sinaga; Fazri Hasiholan Sinaga (Kartika: Jurnal Studi Keislaman, 2026)
Islamic economic literacy is an important factor in the development of the Islamic financial ecosystem in Indonesia. However, a gap still exists between the Muslim community's commitment and their understanding of the implementation of sharia economic principles, including in Pekanbaru City, which has strong Malay-Islamic socio-cultural characteristics. This study aims to analyze da'wah communication strategies, identify barriers, and formulate an effective model for strengthening Islamic economic literacy among urban communities. Using a qualitative approach with a case study method, data were collected through observation, documentation, and review of literacy programs from various institutions. Data analysis employed the Miles and Huberman interactive model. The results show that da'wah communication strategies are implemented through three channels: conventional-cultural (mosques and majelis taklim), contemporary digital, and collaborative-structural (synergy between da'wah institutions, universities, regulators, and the Islamic financial industry). The barriers encountered include limited communicator competence, the complexity of muamalah terms, and low public trust in Islamic financial institutions. This study formulates a Holistic Muamalah Da'wah Model that integrates the strengthening of dai competence, message simplification, the use of digital media, and institutional collaboration